Faba bean flavour and technological property improvement by thermal pre-treatments. (May 2016) - Jiang, Zhong-qing; Pulkkinen, Marjo; Wang, Yu-jie; Lampi, Anna-Maija; Stoddard, Fred L.; Salovaara, Hannu; Piironen, Vieno; Sontag-Strohm, Tuula
Abstract: Food-use of faba bean has been commonly limited by the unpleasant "beany flavour" that can be induced by untreated beans. Pre-treatment of faba beans with microwave heating for different durations and with conventional oven heating was investigated, in order to resolve the "beany flavour" problem. Heating the seeds by microwave for 1.5 min at 950 W was found to be an optimum pre-treatment method that effectively inactivated the endogenous peroxidase and lipoxygenase, which are responsible for the beany flavour causation. In addition, the treatment improved the technological properties of the beans as it decreased seed hardness, improved milling quality, and increased flour pasting viscosity. It slightly decreased protein solubility, while heating with microwave for 2 min or longer decreased the protein solubility more severely and decreased the flour pasting viscosity. Conventional oven heating at 170 °C for 30 min also inactivated the peroxidase and lipoxygenase. The microstructure of the particles in flour-water-suspension was changed by both microwave and conventional oven heating methods, which induced the formation of water-insoluble starch-protein aggregates. Microwave heating for 1.5 min provided an excellent balance of improved milling properties, preserved protein solubility and minimized activity of enzymes that are detrimental to product flavour. Highlights: Faba bean "beany flavour" problem can be solved by thermal pre-treatment. Microwave treatment inactivated faba bean enzymes detrimental to flavour. Treating faba bean with microwave for 1.5 min was found as an optimum method. Microwave treatment improved milling properties of faba beans. Too excessive thermal treatment may reduce faba bean protein solubility.